Legal Implications of Peace Agreement Deeds Made Before a Notary in Resolving Overlapping Land Disputes in The Indonesian Legal System - Lestari, Sri; Suwondo, Denny (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2025)
Abstract. This study aims to determine and analyze the function of a notary based on his position in making a peace agreement deed, to determine and analyze the legal implications of a peace agreement deed made before a notary in resolving overlapping land disputes in the legal system in Indonesia. The research approach method used in this thesis is empirical legal research with a sociological legal approach method. The specifications of this study use qualitative descriptive. The types of data used in this study are primary data including the 1945 Constitution of the Republic of Indonesia, the Civil Code, Law Number 5 of 1960 concerning Basic Agrarian Provisions, Law of the Republic of Indonesia Number 2 of 2014 concerning Amendments to Law Number 30 of 2004 concerning the Position of Notary, as well as secondary data containing books and other supporting documents. Collection of research data using interview techniques and document studies or library materials. The data analysis method used in analyzing data is qualitative analysis. The results of the study show that a Notary is a public official who has a great responsibility in ensuring the validity and fairness in making authentic deeds, one of the legal products made before a notary is a peace agreement deed. In carrying out his/her duties, a notary must be professional, honest, neutral and not take sides with any party in the legal acts he/she carries out. A peace agreement deed made before a notary in the Indonesian legal system is an authentic deed in the eyes of the law which can be used as evidence without relying on a decision, because the authentic deed has permanent legal force. and violations committed by the parties against the contents of the peace agreement can be directly executed based on the strength of legal standing.Keywords: Authentic Deed; Notary; Peace Agreement Deed.